Focal adhesion kinase inhibitor PF573228 and death receptor 5 agonist lexatumumab synergistically induce apoptosis in pancreatic carcinoma - Xiangxuan Zhao; Wei Sun; William M Puszyk; Shannon Wallet; Steve Hochwald; Keith Robertson; Chen Liu (Tumor Biology)
Pancreatic cancer has one of the lowest survival rates of all cancers. The mechanism underlying chemo-resistance of pancreatic cancer is not well understood. Our previous article reported that small molecule YM155 induced apoptosis in pancreatic cancer cells via activation of death receptor 5. In this study, we aim to continuously address death receptor 5–mediated apoptosis in chemo-resistant pancreatic carcinoma. We found that in comparison to paired pancreatic cancer tissues and adjacent normal tissues, five of the six cancer tissues had downregulated death receptor 5 and upregulated Bcl-xL. Mono treatment with lexatumumab was not sufficient to induce apoptosis in pancreatic cancer cells, whereas focal adhesion kinase inhibitor PF573228 significantly sensitized lexatumumab-induced apoptosis. Western blotting analysis revealed that lexatumumab and PF573228 combination treatment increased death receptor 5 but decreased Bcl-xL expression. Interestingly, pre-treatment with Bcl-xL inhibitor ABT263 reversed the insensitivity of panc-1 cells to lexatumumab or PF573228-induced apoptosis. Specific small interfering RNA-mediated gene silencing of Bcl-xL effectively sensitized pancreatic cancer cells to lexatumumab or PF573228-induced apoptosis. Furthermore, lexatumumab and PF573228 combination was shown to exhibit significant xenograft pancreatic tumor growth inhibition in SCID mice. Our data provide fundamental evidence to support the notion that lexatumumab and PF573228 co-treatment could be a potentially effective regime for patients with pancreatic cancer.